Changes in the in vitro ruminal fermentation dynamics of diets for cattle, based on corn grains and different levels of sweet potato (Ipomoea batatas, L.) integral silage - Solis, C.; Rodríguez, R.; Marrero, Y.; Moreira, O.; Sarduy, L.; Ruiloba, M. H. (Cuban Journal of Agricultural Science, 2020)
In vitro ruminal fermentation dynamics of isoenergetic (10.9 MJ ME kg-1) and isoproteic (12.1% CP) diets for cattle were determined, with gradual replacement levels of 0.0 (T0, control), 32.4 (T32), 77.6 (T78) and 100.0 % (T100) of ground corn grain, on a dry basis, mainly by integral sweet potato silage. Accumulated gas production during the 96 h of in vitro fermentation was analyzed with a mixed generalized linear model. the increases in gas production during the initial stage were 73.0, 80.0, 98.0 and 103.8, in the intermediate stage were 82.0, 75.5, 73.2 and 70.5, and in the final were 50.0, 51.8, 45.2 and 44.8 mL g-1 of incubated organic matter (incOM) for T0, T32, T78 and T100, respectively. In the initial stage, the highest increases of T78 and T100 were attributed to the greater availability of soluble carbohydrates and sugars. In the intermediate period, the increase in T0 was explained by the degradation of protein matrix that surrounds corn starch. In the final stage, the lower increases were related to the limited availability of fermentable substrates and microbial recycling. On average, T78 and T100 showed greater fermentative potential (259.2 mL.g-1 incOM), microbial efficiency rate (0.13), maximum speed (12.4 mL.g-1 incOM h-1) and less time to reach maximum speed (9.90 h). It is concluded that, in in vitro conditions, diets with sweet potato integral silage provided greater nutrient availability for ruminal microorganisms, which favors energy supply for the different metabolic processes in the rumen. Key words: fermentation, diets, starch, maximum speed, microbial efficiency